Point de vue : l’autofiction - Robin, Régine (CV Photo)

(untitled) (Les Productions Ciel variable, 1998)
Summary This article discusses the new developments in autobiography, the featuring of the self in literature and photography, in a hybrid genre that Serge Doubrovsky has called "self-fiction." The examples used here are Alain Robbe-Grillet and Roland Barthes, who use photographs as part of their theoretical thought. Self-fiction: an autobiography aware of its own impossibility. Traduction Käthe Roth